Carob fruit extract as naturally products corrosion inhibitor for copper-nickel alloys in brine solutions - Abd El Aziz S. Fouda; Mona Nageeb; Ghalia A. Gaber; Amal S. Ahmed; Ahmed A. El-Hossiany; Mohamed F. Atia (Scientific Reports)
Abstract Copper-nickel alloys are the preferred material for desalination facilities and condensers and heat exchangers that use saltwater as a coolant. The eco-friendly compounds especially Carob fruit extract (CFE) has emerged as excessive green corrosion inhibitor for alloys. Cu-Ni alloys are widely used in various industries due to their excellent corrosion resistance. However, their performance can be compromised in aggressive environments like seawater (which is approximately 3.5% NaCl). To evaluate the corrosion behavior of these alloys and the effectiveness of corrosion inhibitors, researchers often employ weight loss, potentiodynamic polarization, and impedance spectroscopy techniques. The results showed that CFE exhibited a good ability to decrease the CR of alloys in 3.5% NaCl solution. The inhibition efficacy (IE) was reached to 92.6% and ̴ 83.2% at 300 ppm dose of CFE for Cu-10Ni alloy and Cu-30Ni alloy, respectively. The CR increases with temperature rising, but the addition of CFE reduces the CR, and the reduction depends on the dose of the extract. Adsorption of the extract gives a good fit to Langmuir, Temkin, and Freundlich isotherms model. The free adsorption energies of CFE on Cu-10Ni and Cu-30Ni alloys were 17.61 and 15.86 kJ mol−1, respectively, suggesting that CFE was weakly held to both alloys. The presence of a protective film on the alloys surface is confirmed by using scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy and atomic force microscope (AFM). The study suggests that utilizing affordable, natural substances as green corrosion inhibitors presents a new strategy for promoting both resource efficiency and environmental sustainability.